The research on the west side of the hittite emperial ruins in Sivas-Altinyayla (Kupkli-Sarissa) - (:unkn) unknown (IEEE, 2006)
In recent years, geophysical approaches are being frequently used in modelling and in pre-process before the excavation of archeological ruins. Magnetic approach has been used in the archeological ruins in Sivas- Altinyayla, Turkey. The boundaries of the buried structure is being detected by wavelet methods to the total magnetic anomaly map.